Kratka zgodovina vakuumske tehnike - Južnič, Stanislav (Vakuumist, 1999)
The article enumerates the basic advancement of vacuum pumps and other elements of vacuum systems. Parallel with the fundamental research we describeareas of vacuum technology application and manners with which they mutually stimulate each other. We also describe application and later researchof vacuum technology in Slovenian territory.
Keywords: vakuumska tehnika; zgodovinski pregledi